1969
DOI: 10.1172/jci106122
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of plasma free fatty acid and triglyceride metabolism in man

Abstract: A B S T R A C T Plasma transport of free fatty acids (FFA) and triglyceride fatty acids (TGFA) was studied in seven subjects with normal lipid metabolism, one case of total lipodystrophy, and one case of familial hyperlipemia (Type V). Studies were carried out after intravenous injection of radioactive FFA, of lipoproteins previously labeled in vitro in the triglyceride moiety, or both.Computer techniques were used to evaluate a series of multicompartmental models, and a general model is proposed that yields o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
69
2
1

Year Published

1976
1976
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(82 citation statements)
references
References 35 publications
(30 reference statements)
9
69
2
1
Order By: Relevance
“…However, no attempt was made to separate individual lipoproteins before performing the labeling procedure; in fact, the authors reported that radiolabeled TG was found in all lipoprotein fractions before injection of the processed sample. In a recent elegant study, Sidossis and coworkers (3) used in vivo labeling of VLDL-TGs using [U- 13 C 3 ]glycerol, plasmapheresis, and isolation of 13 C-labeled VLDL-TGs followed by traditional isotope dilution technique (primed constant infusion and steady-state equations). Such studies require the availability of mass spectrometry facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no attempt was made to separate individual lipoproteins before performing the labeling procedure; in fact, the authors reported that radiolabeled TG was found in all lipoprotein fractions before injection of the processed sample. In a recent elegant study, Sidossis and coworkers (3) used in vivo labeling of VLDL-TGs using [U- 13 C 3 ]glycerol, plasmapheresis, and isolation of 13 C-labeled VLDL-TGs followed by traditional isotope dilution technique (primed constant infusion and steady-state equations). Such studies require the availability of mass spectrometry facilities.…”
Section: Discussionmentioning
confidence: 99%
“…These methods do not allow one to determine the metabolic fate of the fatty acid moiety of the TG molecule and are dependent upon the validity of the mathematical model for the given experimental setting. Another approach is to collect and isolate in vivo-labeled VLDL particles and reinfuse them into the same subject at a later time (13). However, using this approach, only a small amount of labeled VLDL-TG can been obtained for reinfusion; consequently, the specific activity (SA) of circulating VLDL-TG after reinjection has been sufficiently low that it is sometimes difficult to obtain accurate kinetic estimates.…”
mentioning
confidence: 99%
“…Early studies of FFA kinetics used the approach of measuring FFA radioactivity and concentrations. FFAs were isolated from plasma with extraction (27)(28)(29)(30), and separate aliquots were assayed for radioactivity (dpm/ml) and fatty acid content (nmol/ml). By dividing the former by the latter, FFA SA (dpm/nmol) was calculated.…”
mentioning
confidence: 99%
“…We speculate, first, that other fat depots in the body may have been responsible for the increase in FFA levels after LPS in the diabetic group. Thus, while the abdominal subcutaneous fat depot is usually considered the main source of FFA into plasma [29], a small proportion arises from leg and intra-abdominal adipose tissue [30][31][32]. Secondly, we propose that the attenuated LPL and HSL expression response in the subcutaneous adipose tissue in patients with T2DM encompasses compensatory mechanism that serves to limit the systemic levels of FFA upon pro-inflammatory stimuli.…”
Section: Genmentioning
confidence: 87%